The Role of Parents in Educating Adolescents in Sidoarjo Regency - Abdulloh Masud; Anita Puji Astutik (Indonesian Journal of Cultural and Community Development, 2022)
This research was carried out in Dukuhsari Village, Jabon District, Sidoarj Regency. In recent times juvenile delinquency has increasingly shown a very worrying behavior which is caused because parents are busy working so that parents pay less attention to their children. The problem being researched is what is the role of parents in educating teenagers in Dukuhsari Village? And is there a decrease in the role of parents in educating teenagers in Dukuhsari Village?. This research is a qualitative research with the type of field research. Data collection techniques in this study use techniques such as observation, interviews and documentation. From the results of this study, the types of juvenile delinquency in Dukuhsari were stealing, drug use of methamphetamine, and liquor. Juvenile delinquency occurs due to lack of parental supervision and minimal inculcation of religious values ​​so that they are affected by the surrounding environment.